A Centralized Automated System of Monitoring Adverse Events of Medications- “Medreminder” - Serikzhan Berdakhovich Sydykov (Journal of Global Pharma Technology, 2019)
Research ObjectiveTo develop and test the methodology of the centralized automated system of monitoring adverse events of medications in the Republic of Kazakhstan.Research TasksThe analysis of the existing practice of monitoring adverse events of medication in the Republic of Kazakhstan, the identification of problems and the directions to improve the situation.Testing the models of an automated system collecting information about adverse events of medications and the evaluation of effectiveness of the developed system collecting information about adverse events of medications, identifying patients/consumers’ roles of Kazakhstan medical products in the system of pharmacovigilance.Keywords: pharmacovigilance, monitoring the safety of medications, patients, consumers, monitoring adverse events, “yellow card”, consumer reporting.